The Concept of Indefinite Sentence in the General Election Criminal Accountability System in Indonesia - Lubis, Mhd Teguh Syuhada (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
General Elections are a means of popular sovereignty to elect members of the People's Representative Council, members of the Regional Representative Council, President and Vice President, and to elect members of the Regional People's Representative Council, which are carried out directly, publicly, freely, secretly, honestly and fairly in the Unitary State The Republic of Indonesia is based on Pancasila and the 1945 Constitution of the Republic of Indonesia. It is known that based on the latest regulations, the implementation of general elections in Indonesia is regulated in the provisions of Law Number 7 of 2017 concerning General Elections. These laws and regulations not only regulate the systematics of holding general elections but also regulate norms regarding the prohibitions and obligations of each legal subject in holding general elections. This includes criminal law rules that regulate it. So far it is known that the criminal provisions in the General Election Law only adhere to the Indefinite Sentence punishment system, namely that the criminal threat is only regulated to a maximum and there is no minimum criminal threat limit. Such a criminal system brings problems in implementing criminal liability for perpetrators of election crimes from a regulatory perspective. Therefore, it is necessary to look further at the basic concept of criminal liability in general elections, as well as the application of the indefinite sentence concept to general election crimes in Indonesia. The research method used in this research is normative juridical research and the approach is based on legal rules and regulations. Furthermore, the nature of this research is descriptive analysis. The data sources used to conduct this research come from secondary data which uses legal materials in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection tool in this research is library research. And finally it will be analyzed using qualitative analysis. Based on the research results, it is known that in principle the criminal provisions contained in general election crimes adhere to the indefinite sentence system, this can be seen in the criminal provisions starting from Article 488 to Article 554 of Law Number 7 of 2017 concerning General Elections which as a whole only outline maximum criminal sanctions and does not specify the minimum criminal sanctions provisions. Law makers should construct the provisions of the criminal system in the General Election Law using an indeterminate sentence pattern or minimum criminal threat. So that there is legal certainty and legal benefits that can be applied by the Panel of Judges to the electoral crimes that occur